Bionomics And Host Range Of American Serpentine Leaf Miner liriomyza trifolii (burgess) (agromyzidae :diptera) - Smitha M K (Department of Agricultural Entomology, College of Horticulture, 2003)
The present investigation on the "Bionomics and host range of American serpentine leaf miner, Liriomyza trifolii (Bugcss) (Agrornyzidae: Diptera)" was undertaken in the Department or Entomology, College of Horticulture, Vellanikkara during 2001-2002. Field surveys and laboratory studies were carried out with the objective of studying the biology, host range, natural enemies and seasonal incidence of L. trifolii. The biology of L. trifolii was studied by releasing a pair of one day old adult l1ies 10 the rearing cages where cow pea seedlings were kept as host plants and honey as a food source. The female Ily inserted its eggs in the tubular punctures made on the leaves with its pointed ovipositor. The oval, translucent, milky white eggs hatched in about 2.08 days. The larvae mined the upper leaf surface and produced characteristic serpentine mines. There were four larval instars having a total duration of 3.4days. Alter the larvae attained full size or 2.35 mm length and (),(i4 mill width it made a semicircular cut at the broad end of the leaf mine. Through this cut larva came out of the mine and fall down to the soil for pupation. Inside the soil the larva turned to golden yellow coloured pupa. Female pupa was larger compared to male pupa. Adult emergence took place after 7.9 days. The adults had a longevity varying form 4.5days for mall's and 7.4 days for females where as they were feed with 2 per cent honey solution. Adult females were larger than the males and had black pointed spot on the lower sick of last abdominal segment. The fecundity of female varied from 14.6 eggs per day per female. The adult female laid about 48-5'0 eggs in its life time. The ratio or oviposition or feeding puncture was I: R.QC) to 1: 9.3. The total life cycle from eggs to adult took 13.3 days. The host range was studied by conducting surveys at regular intervals. 48 host plants belonging to 13 plant families were reported as host plants of this pest. It is a highly polyphagous insect and majority or the host plants belonged to families of Cornpositac and Cucubitaccae. The intensity of infestation of 1.. trifolli on various crops were calculated by counting the number of larval mines per leaf on the upper, middle and lower leaves of the plants. The attack of L. trifolt! was more on the lower leaves compared to middle and top leaves. Cowpea was found to be the most preferred host plant of L.